Health Resorts and Their Importance for the Development of Less Developed Areas in Slovenia - Horvat, Uroš (Journal for Geography, 2010)
In the paper is presenting the importance of health resorts for the development of less development areas in Slovenia. Health resorts are one of the oldest kinds of tourist resorts and started to develop in Slovenia already in 18th and in the beginning of 19t h centuries. The main reasons for the first tourists’ visits were connected with bathing in thermal waters, drinking of healing water, socializing of the higher social classes and entertainment. Later, the health resorts became centres of highly qualified medical rehabilitation based on the basis of using of natural remedies and modern medical treatments. The so called classical health resorts prevailed in Slovenia until the mid-1980s. The beginning of the 1990s marked an important turnabout in the development of health resorts in Slovenia. With the construction of modern swimming pools, some health resorts have started to use thermal water for fun and “experience”. The so called “thermal rivieras” or “thermal parks” have emerged with covered or open pools, which are open throughout the year. The reorientation to mass tourism based on recreation, healthy lifestyle, wellness etc., as well as spending of holidays in apartment accommodation have significantly increased the tourist visits in the so called recreation health resorts. These are usually located in less developed areas of the country, which means their importance is even greater for the employment of the inhabitants and the spatial and functional development of rural areas. In the case study author is orientated especially on the development of the health resorts in the Posotelje region (in NE Slovenia).
Keywords: tourism; health resort; spa; less developed areas; Slovenia